Chimeras of the Past and Navigation through the Latest Development Conditions, Risks and Opportunities for Managing the Russian Arctic - Tatyana P. SKUFYINA; Elena A. KORCHAK; Sergey V. BARANOV (Arctic and North, 2021)
The uniqueness of today's social processes triggered by the COVID-19 pandemic determines the lack of insights into the transformation of the socio-economic space of the Russian Arctic. The purpose of this article is to review the past, recent, and future conditions for development and management of the Russian Arctic, considered in the context of the unfolding crisis of a non–economic nature and its consequences. The methodological peculiarity of the review is presentation of the phenomenon of the current crisis in the context of interrelated fundamental problems of the development of the Russian Arctic, the new economic reality, which makes it difficult to reliably predict the future. This naturally led to the substantiation of a series of contradictions and difficulties in implementing the declared development goals of the Russian Arctic, that are specifically reflected in the title of the article — "chimeras", which in biology means an organism consisting of genetically heterogeneous cells. A statistical description of the specifics of socio-economic development of the Arctic regions under the COVID-19 pandemic has been carried out in the context of review of the support measures, examination of the economic structure and the corresponding scale of "disconnection" of the regions' economies during the period of isolation and the subsequent recovery. It is revealed that the Arctic regions demonstrate greater economic resilience compared to the overall Russian situation, which is associated not so much with the strengthening of stabilization measures at the federal level with the support of the regional level, but with the fundamental reasons — the relative simplicity of the Arctic extractive economy, higher population incomes, low level of small and medium business development. Navigation on the risks and opportunities of governing the Russian Arctic has been carried out, linking the fundamentals and the practical implications of the study through the traditional rationale for navigating and considering the ...